Povo Karajá de Aruanã/GO : território e vida indígena - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The Karajá, also known as water People, have in Araguaia the material and immaterial basis of life. According to its myth of origin, it is from the depths of the waters of the Araguaia River that all Karajá life had its origin and went out to inhabit the dry part of the land. This people, like most of the indigenous peoples of Brazil, with the arrival of the colonizers, had their history marked by the process of territorialization, with the expropriation and or decimated of their territories. According to data from the National Foundation for Indigenous Health (FUNASA, 2020), in Brazil, Karajá villages total 29 in total, with a population of approximately 4,000 indigenous people, distributed in the states of Goiás, Tocantins and Mato Grosso. The Karajá de Aruanã whose territory was diminished with the implantation of the Leopoldina village, attributing to this people a fragmentation of their territory, imposed by the advance of agribusiness and recently by tourism. With so many impositions on their culture, even though the villages are in connection with the city, they keep their cultural organizations very strong. This research aims to analyze the fragmentation of the territory and of the socio-cultural relations of the Karajá people located in the municipality of Aruanã, in the State of Goiás. Karajá in the reproduction of your life and culture? The research is qualitative, based on the methodological procedure of participant observation with the basic component of fieldwork, conversation circles and records of narratives and images.
Karajá people of Aruanã/GO : territory and life indigenous
Keywords: Karajá de Aruanã; Vida indígena; Território; Cultura; Karajá de Aruanã; Indigenous life; Territory; Culture; CIENCIAS HUMANAS::GEOGRAFIA; GEOGRAFIA HUMANA::GEOGRAFIA DA POPULACAO